Integrated Supply Chain Contract Model With Drop-Shipper Players - Faisal Ibrahim (Jurnal Teknik Industri, 2018)
In this paper, we developed model integrated supply chain model with drop-shipper players.  The aim of the study is to integrate players in the supply chain system that one of its players is a drop shipper. This coordination model considers the policy of late payment and prosecution for delivery of goods. Previous, The author has described the supply chain system in detail. The experiments were conducted into different case scenarios, where each scenario would represent the actual system that occurred. Then also conducted sensitivity analysis on some predicted variables significantly influence the total cost of the supply chain. From the results obtained, it can be concluded that coordination with consideration of delay in payment and penalty contract for drop ship has successfully integrated the players in the supply chain system under study. This can be proved by the lower total cost of the supply chain when it is integrated with that consideration.